A likely pathogenic variant in the SLC20A2 gene presenting with progressive myoclonus. Issue 3 (1st February 2019) - Lamquet, Simon; Ramos, Eliana M.; Legati, Andrea; Coppola, Giovanni; Hemelsoet, Dimitri; Vanakker, Olivier M.
Abstract: A 60‐year‐old man is presented with progressive involuntary muscle movements and neuropsychiatric symptoms who developed a variety of additional complaints over 2 years. Brain imaging revealed bilateral basal ganglia calcifications suggesting primary familial brain calcification. Analysis of the SLC20A2 gene revealed a missense mutation (c.541C>T, p.(Arg181Trp)), in silico predicted to be deleterious and not found in available databases. Segregation analysis confirmed his asymptomatic father to harbor the same mutation, though on brain imaging basal ganglia calcifications were found. This report illustrates the intrafamilial variability of the phenotype and generalized myoclonus as the presenting symptom.